Enhanced activity of bimetallic Pd-Ni nanoparticles on KIT-6 for production of hydrogen from dodecahydro-N-ethylcarbazole. (1st December 2022) - Feng, Zhaolu; Bai, Xuefeng
Graphical abstract: Highlights: Bimetallic Pd-Ni/KIT-6 catalyst was prepared by inorganometallic chemistry and sonochemistry. Tiny Pd-Ni NPs are obtained by metal ion anchoring and complexation of metal with O. Synergy between ultrafine size and inter metallic electron transfer of Pd-Ni NPs enhances the catalytic performance of Pd-Ni/K6. The hydrogen productivity over Pd4 Ni1 /K6 is 1.7 times higher than that of Pd/K6. Abstract: The development of catalysts with excellent dehydrogenation performance is the key to solving the problem of slow dehydrogenation and high temperature in the liquid organic hydrogen carrier hydrogen storage cycle. The bimetallic Pd-Ni/K6 catalyst was prepared by inorganometallic chemistry adsorption (ICA) and ultrasonic-assisted isopropanol reduction. Pd(NH3 )4 2+ and Ni 2+ will be anchored at the location of silanol groups (Si-OH) on the surface of KIT-6 (K6) by ICA, which prevents the aggregation of bimetallic Pd-Ni nanoparticles (NPs) during ultrasonic reduction. The HADDF-STEM results showed that Pd-Ni NPs with an average particle size of 2.1 nm were uniformly dispersed on the K6 surface. Pd-Ni alloy structure was found in Pd4 Ni1 /K6, and there was obvious electron transfer from Ni to Pd. The small Pd-Ni NPs, the electronic interaction of bimetallic Pd-Ni NPs, and the lattice defects caused by the Pd-Ni alloy enhance the activity of Pd4 Ni1 /K6 for H12-NEC dehydrogenation. At 180°C, the hydrogen productivity over Pd4 Ni1 /K6 is 1.7 times higher than that of Pd/K6. The complexation of Pd and Ni with O of Si-OH stabilized Pd-Ni NPs and prevented their agglomeration and leaching. Pd4 Ni1 /K6 showed excellent cycle stability, and the dehydrogenation efficiency remained above 90 % after 5 cycles.